The Effect of a proposed teaching Program on Developing Mathematical Thinking Skills among Kindergartens students in Kuwait - Alfadly, Yasmeen; Abu loum, Khaled (DIRASAT: EDUCATIONAL SCIENCES, 2016)
The study aimed to identify the effectiveness of a proposed teaching Program on Developing Mathematical Thinking Skills among Kindergartens students in Kuwait. The study followed the semi-experimental method, the sample consisted of experimental groups and the number (25) students, and the same for the control group were randomly selected from public kindergartens management education capital of the State of Kuwait. To achieve the objectives of the study was to develop a program to experience pedagogy (religion of Islam), and Testing in mathematical thinking. The results of the study showed the following: There are significant differences between the average of the experimental group that studied using the teaching program and signs of the control group, who studied in the usual way on Mathematical Thinking Skills in favor of the experimental group marks. In the light of the outcome of the results of the study the researcher made a series of recommendations, including: the use of the teaching program by kindergarten teachers, and circulated to public kindergartens affiliated to the Ministry of Education in Kuwait.